RAG recombinase expression discriminates the development of natural killer cells - Sprissler, Jasmin; Pannicke, Ulrich; Rump, Eva-Maria; Schrezenmeier, Hubert; Casadei, Nicolas; Pogoda, Michaela; Kuhlburger, Laurence; Oquendo, Morgana Barroso; Czemmel, Stefan; Debatin, Klaus-Michael; Erlacher, Miriam; Schwarz, Klaus; et al. (Frontiers in Immunology, 2025)
IntroductionV(D)J recombination, initiated by recombination-activating gene (RAG) endonucleases, is a crucial process for the generation of diversified antigen receptors of T and B lymphocytes but regarded dispensable for innate natural killer (NK) lymphocytes lacking clonotypic receptors.MethodsTo explore the impact of potential rearrangements on NK cell maturation, RAG-fate mapping reporter human induced pluripotent stem cell (iPSC) lines were generated by introduction of RSS-invEGFP constructs into the AAVS1 locus using CRISPR/Cas9 and differentiated into NK cells in vitro.ResultsGFP expression was observed in up to 14% of mature NK cells characterized by a CD45dim CD56dimCD57+NKG2C+/−KIR+/− phenotype and unproductive genetic rearrangements in the IGH locus. Advanced maturation was further revealed by transcriptomic studies using RNA sequencing. Despite their strong effector function, DNA damage response and survival to ionizing radiation were compromised.DiscussionThese findings suggest a role of RAG expression in NK cell ontogeny supporting the development of a terminally differentiated effector population.